Oral immunotherapy for cow’s milk allergy in children: a systematic review and meta-analysis - Wang, Yan; Liu, Shunli; Lu, Meizhu; Guo, Jingyu; Lv, Can; Huang, Lan (Frontiers in Immunology, 2025)
ObjectiveCow’s milk allergy (CMA) is one of the most common causes of food allergies (FA) in children. There have been studies on the use of immunotherapy in cow’s milk protein allergy, with oral immunotherapy (OIT) being the most extensively researched. We conducted a comprehensive analysis of randomized controlled trials (RCTs) to explore the efficacy and safety of OIT to manage cow’s milk allergy in children.MethodsPubMed, EMBASE, Cochrane Library, and Scopus databases were searched from their inception until August 2024. Randomized controlled trials that reported on the efficacy or safety of IT for CMA were included. Two investigators independently extracted data on regimen of intervention, outcomes, number of cases and gender ratio. Pooled estimates of relative risks or standardized mean differences with 95% confidence intervals were calculated from the included studies for dichotomous and continuous outcomes.ResultsNineteen RCT articles (815 participants) were included. The meta-analysis indicated that oral immunotherapy significantly facilitated desensitization in patients with cow’s milk allergy in children (relative risk [RR] 2.51, 95% CI: 1.54–4.09, I²=84.4%). Tolerance threshold at oral food challenges (OFC) increased following oral immunotherapy compared with a standard mean difference (SMD) of 3.58 (2.82–4.33). After oral immunotherapy, the antibody titers of cow milk protein sIgE (SMD -0.42, 95% CI: -0.72 to -0.11, I²=28.8%) and casein sIgE (SMD -0.54, 95% CI: -0.97 to -0.11, I²=0%) decreased. The risk of adverse reactions with immunotherapy was not higher than that in the control group, with an RR of 2.05 (95% CI 0.96–4.37, I²=81.5%).ConclusionsOral immunotherapy, is associated with desensitization to CMA in children, without increased risk of short-term adverse events, but late complications such as eosinophilic esophagitis require caution. More high-quality studies are needed to explore the long-term efficacy of OIT for CMA.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD42024541769.